Analisis behavioral intention pada layanan aplikasi GoApotik - Wibowo; Lina (Universitas Tarumanagara, 2023)
The present era is also known as the information age, where humans need information. The existence of the internet on smartphones makes it easier for humans to get information and shop wherever and whenever related to drug needs. One of the online pharmacy services in Indonesia is the GoApotik application, which is a digital healthcare startup that applies the principles of distribution and pharmaceutical services, especially drugs through e-commerce. Through this application, users can search for various information and make it easier for the public to get medicines and health equipment, through digital platforms in a definite and safe manner. This study measures the interest of GoApotik application users in Indonesia using the modified UTAUT2 research model, where researchers analyze the variables of performance expectancy, effort expectancy, social influence, facilitating condition, hedonic motivation, and health literacy on Behavioral Intention. The data used in this study were 246 respondents who were obtained online using a questionnaire. Respondents are users of the GoApotik application. Researchers used Structural Equation Modeling (SEM) using SmartPLS software version 3.0 to test the hypothesis. The results showed that effort expectancy, facilitating conditions, and health literacy had a positive influence on behavioral intention. In the moderator variable, the gender variable affects the performance expectancy factor and age affects the effort expectancy factor. This study resulted in an R2 value of 0.624 and was included in the moderate category. Era masa kini disebut juga sebagai era informasi, dimana manusia sangat membutuhkan informasi. Adanya internet pada ponsel pintar semakin memudahkan manusia untuk mendapatkan informasi maupun belanja dimana pun dan kapan pun terkait kebutuhan obat. Salah satu layanan apotek online di Indonesia, yaitu aplikasi GoApotik yang merupakan digital healthcare startup dan menerapkan prinsip-prinsip penyaluran serta pelayanan kefarmasian khususnya obat-obatan melalui e-commerce. Melalui aplikasi ini, pengguna dapat mencari berbagai informasi dan mempermudah masyarakat mendapatkan obat-obatan serta perlengkapan kesehatan melalui platform digital secara pasti dan aman. Penelitian ini mengukur minat pengguna aplikasi GoApotik di Indonesia dengan menggunakan model penelitian UTAUT2 yang telah dimodifikasi, dimana peneliti menganalisis variabel performance expectancy, effort expectancy, social influence, facilitating condition, hedonic motivation, dan health literacy terhadap behavioral intention. Data yang digunakan dalam penelitian ini sebanyak 246 responden yang didapatkan melalui online menggunakan kuesioner. Peneliti menggunakan Structural Equation Modeling (SEM) dengan menggunakan software SmartPLS versi 3.0 untuk menguji hipotesis. Hasil penelitian menunjukkan bahwa effort expectancy, facilitating conditions, dan health literacy memiliki pengaruh positif terhadap behavioral intention. Dalam variabel moderator, maka variabel gender berpengaruh pada faktor performance expectancy dan age berpengaruh pada faktor effort expectancy. Penelitian ini menghasilkan nilai R2 sebesar 0,624 dan termasuk kategori moderat.